ONLINE TEACHING IN ARCHITECTURAL EDUCATION: A BOON OR BANE? - Patra, Bikash; Patnayaka, Ravindra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid advancement of technology has led to a paradigm shift in the field of education, and architectural education is no exception. The advent of online teaching methods has opened new possibilities and challenges for both educators and students. The integration of online teaching methods in architectural education has sparked considerable debate. This study examines the advantages and drawbacks of online learning, drawing insights from both faculty and student perspectives. Through a comparative analysis of the response from faculty and student survey from various architecture colleges in India, this paper aims to shed light on the key factors that determine the feasibility of online teaching in architectural education. Through comparative analysis, authors explore the impact of virtual classrooms on teaching standards, student engagement, and overall learning outcomes. These findings shed light on the following key aspects: Flexibility and Adaptability, Effective Communication, Assessment Strategies, Technological Challenges, and hybrid approach.